Improving Mathematical Ability and Skill Using Microsoft Excel in SMP Kristen Kefamenanu - Simarmata, Justin Eduardo; Mone, Ferdinandus; Bete, Hendrika; Naimnule, Maria; Bone, Dominifridus; Chrisinta, Debora (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2023)
Microsoft excel is application that used as a learning aid in schools. The use of microsoft excel has been very commonly used in education activity. Microsoft excel is very useful to help learning process for students and educators. Microsoft excel has been known as a spreadsheet worksheet application program that is very helpful in data processing and reporting activities. It is equipped with calculation and graph creation features in the form of a number processor with various formulations to process data automatically including basic calculations, data management and data creation. SMP Kristen Kefamenanu had many students in the school that are still who do not understand and skilled in using computers. The lack of use of computers in learning materials except for Learning Information Technology and Computers (ICT) which is generally used as an extracurricular subject. The purpose of this community service activity is to introduce microsoft excel as a mathematics learning tool carried out at SMP Kristen Kefamenanu. The results of the activity can be knowing the basics of microsoft excel and finding mean values, median and single data mode with microsoft excel. At every lesson activity that has been conducted, students can show improvement in operating microsoft excel and can be seen from the test results provided.